The Creative Thinking Process of Elementary School Students in Solving Mathematics Story Problems Reviewed from Learning Styles - Ai Mulyani; Entit Puspita; Dyah Lyesmaya (The Eastasouth Journal of Learning and Educations, 2026)
Current elementary school mathematics instruction tends to be procedural and homogenous, thus under-facilitating diverse learning styles and impacting students' low mathematical creative thinking skills in solving word problems. This study aims to in-depth describe elementary school students' creative thinking processes in solving math word problems, considering their visual, auditory, and kinesthetic learning styles. Using a qualitative approach with a phenomenological design, this study involved sixth-grade students at Pamuruyan 9 Elementary School, Sukabumi Regency. The sample was selected using a snowball sampling technique based on a learning style questionnaire, resulting in six students representing the three dominant learning modalities. Data analysis applied Moustakas' phenomenological model (epoche, horizontalizing, categorization, textual-structural description, and conclusion drawing). The results showed that elaboration was the most dominant indicator across all subjects, while fluency and flexibility showed the greatest variation across learning style groups. The novelty of this study lies in its comprehensive mechanistic mapping of the navigation of creative components based on learning modalities at the elementary school level. The implication emphasizes the importance of implementing differentiated learning based on learning styles to optimize students' potential and mathematical creative thinking abilities.